Soothing Rooms Reduce the Need for Restraints for Inpatient Mental Health Patients - Nierengarten, Mary Beth (MD Conference Express, 2015)
Implementation of soothing rooms for adults and adolescents in an acute mental health unit in a Midwestern regional hospital resulted in a 35% reduction in the use of restraints among the adult patients, demonstrating a benefit to both patients and mental health nurses by reducing restraint usage and suggesting a new standard of care. The effectiveness of soothing rooms was evaluated in an acute 32-bed mental health care unit at the SwedishAmerican Center for Mental Health, Rockford, Illinois, USA, and is discussed in this article.